(3GdYedjGJ GdEOGQjI (B/s - (3YdjGf, QHMj eUWais ((3YeGf(B: s (3OGQ UaGA(B, s, 2010)
(3eaghe GdGOGQI h GdYedjGJ GdGOGQjI , GdJNWjW , GJNGP GdbQGQGJ GdGOGQjI , GdJfXje , GdJhXja h Jbjje COGA GdYGedjf , GdJhLjg h GdbjGOI h GdQbGHI h GdGTQGa h GdJfSjb , GdGJUGd GdGOGdGj h GNjQG JOQjH GdYGedjf CKfGA GdNOeI (B.s
(3eQGLY U(B.299s
Keywords: (3EOGQI GdCYeGds; (3GdGOGQIs